PENGARUH PEMBELAJARAN QUIZ TEAM DITINJAU DARI MOTIVASI BELAJAR DAN HASIL BELAJAR - Muhammad Asran; Aprisal Aprisal; Amran Yahya (Program Studi Pendidikan Matematika, 2023)
This study aims to elucidate quiz team learning based on learning motivation and students' mathematics learning outcomes. The type in this study is experimental research. The research design was quasi-experimental with a nonequivalent control group design. The population in this study were all class VIII students at SMP Negeri 1 Tinambung for the 2022/2023 academic year. Sampling in this study uses a simple random sampling technique. Data were analysed using independent sample t-tests and post hoc tests (t-benferroni). The resulting study showed that there were differences in quiz team learning and conventional learning based on learning motivation, there were differences effect of quiz team learning and conventional learning based on student mathematics learning outcomes, and quiz team learning was better than conventional learning based on learning motivation and student mathematics learning outcomes.